2003
DOI: 10.1016/s0164-1212(02)00053-5
|View full text |Cite
|
Sign up to set email alerts
|

A controlled experiment on inheritance depth as a cost factor for code maintenance

Abstract: In two controlled experiments we compare the performance on code maintenance tasks for three equivalent programs with 0, 3, and 5 levels of inheritance. For the given tasks, which focus on understanding effort more than change effort, programs with less inheritance were faster to maintain. Daly et al. previously reported similar experiments on the same question with quite different results. They found that the 5-level program tended to be harder to maintain than the 0-level program, while the 3-level program w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…suggested that inheritance should be used with care and only when needed. In two controlled experiments, Prechelt et al, (2003) reported that maintenance effort was positively associated with inheritance depth. In terms of further empirical studies into inheritance, Chidamber et al, (1998) empirically studied three commercial OO systems none of which showed significant use of inheritance.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…suggested that inheritance should be used with care and only when needed. In two controlled experiments, Prechelt et al, (2003) reported that maintenance effort was positively associated with inheritance depth. In terms of further empirical studies into inheritance, Chidamber et al, (1998) empirically studied three commercial OO systems none of which showed significant use of inheritance.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…The multi-method study of Wood et al, [25] suggests that inheritance should be used with care and only when needed. Finally, two controlled experiments by Prechelt et al [24] found that it took longer to maintain a program with higher levels of inheritance than a program containing fewer inheritance features.…”
Section: Related Workmentioning
confidence: 99%
“…Statistically significant results suggested that a class located deep in the inheritance hierarchy (given by its DIT) was more faultprone than a class higher up in the hierarchy; the study suggested that extensive use of inheritance could have had the opposite effect to that of aiding the maintenance process. Prechelt et al [Prechelt03] suggest that maintenance effort is positively associated with inheritance depth (i.e., the deeper the inheritance hierarchy, the more maintenance effort required -and this would suggest that this is where the potential for faults to be invested lay). Wood et al [Wood99] advise that inheritance should be used with care and only when needed.…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…The extent to which these benefits can be realized is an issue of significant interest for exploratory, empirical software engineering studies. A number of studies have also cast doubt on the extent to which deep levels of inheritance assist with the maintainability of a system [Prechelt03,Cartwright00,Harrison97,Basili96].…”
Section: Introductionmentioning
confidence: 99%